2013
DOI: 10.1111/1467-9566.12007
|View full text |Cite
|
Sign up to set email alerts
|

The family meal panacea: exploring how different aspects of family meal occurrence, meal habits and meal enjoyment relate to young children’s diets

Abstract: The general consensus in the research to date is that family meals are linked to healthier eating habits in children, compared to not eating with the family. Yet, few studies explore what it is about commensality which leads to better food choices among children. Using a representative Scottish sample of five-year-old children, this research explores the extent to which family meal occurrence, meal patterns regarding where, when and with whom children eat and perceived meal enjoyment predict the quality of chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0
10

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 41 publications
5
43
0
10
Order By: Relevance
“…Conversely, olive oil is an expensive item that is less accessible for low-income households in which cost is a key factor in food choice. Such a conclusion is consistent with a study that reported a poorer diet among 5-year-old children from less advantaged backgrounds (37) . A strength of our study is the stratified randomization process for selecting schools for intervention, which decreases the chance of bias in the study sample.…”
Section: Discussionsupporting
confidence: 92%
“…Conversely, olive oil is an expensive item that is less accessible for low-income households in which cost is a key factor in food choice. Such a conclusion is consistent with a study that reported a poorer diet among 5-year-old children from less advantaged backgrounds (37) . A strength of our study is the stratified randomization process for selecting schools for intervention, which decreases the chance of bias in the study sample.…”
Section: Discussionsupporting
confidence: 92%
“…The results from a recent representative Scottish study showed that eating family foods was the most important aspect of family meals associated with a healthier diet at age 5 years (ie, it is the food choice that has greater importance than the form and function of the meal) 42. In our survey, the ‘adherent BLW’ infants were having a greater amount of family foods, as well as less commercially purchased food, whereas the families who followed the ‘parent-led feeding’ method reported a greater proportion of commercially prepared food.…”
Section: Discussionmentioning
confidence: 99%
“…The revised diagnosis has been expanded to include significant food avoidance and restriction, with or without an associated medical condition (Kenney & Walsh, 2013). In the broader social context, the rise in consumption of 'children's food' has further fuelled scrutiny over restricted diets and the replacing of fruit and vegetables with processed foods (Skafida, 2013). The specific label of picky eating is a relatively recent theoretical development and, as such, there are few studies exploring picky eating and 'pickiness' remains a disparately theorised construct (Dovey et al, 2008).…”
Section: Introductionmentioning
confidence: 99%